Androgen Receptors in Resected Ductal Carcinoma In Situ of Breast: Novel Insights With Possible Implications for Testing and Targeted Endocrine Chemoprevention Trials. Issue 5 (May 2019) - Oshilaja, Olaronke; Nomani, Laila; Calhoun, Benjamin C.; Montero, Alberto J.; Sturgis, Charles D.
Abstract : Mammary ductal carcinoma in situ (DCIS) is classically treated by combinations of excision, radiation, and endocrine therapy, based upon the specific needs of individual patients. Estrogen receptor (ER) status is generally assessed by immunohistochemistry (IHC) in newly diagnosed cases of DCIS, and endocrine therapy in this setting is thought to be chemopreventive. The potential impact of androgens on mammary carcinogenesis has been studied in recent years, and several authors have proposed androgen receptor (AR) IHC testing and targeted antiandrogenic therapy in patients with locally advanced or metastatic triple-negative invasive breast cancer (ie, negative for ER and progesterone receptor and HER-2). Very little has been published on AR in DCIS. We report results of AR IHC on archival tissue blocks from 221 adult female patients, each of whom underwent definitive breast resection of DCIS. Of the 221 cases, 72 (33%) were shown to express AR in their DCIS at or above the 10% threshold often used for invasive carcinoma. AR expression was seen in all grades of DCIS. Of the 72 positive AR cases, 21 (29%) were ER negative, corresponding to 10% (21/221) of all patients. The majority of the AR-positive cases were high grade, and the most common histologic subtype in this subset was a solid growth pattern with apocrine features. Early data from clinical trials evaluating AR antagonists in invasive/metastatic triple-negative breast cancer suggest that some patients may benefit from androgen blockade. IHC testing and potential clinical trials of AR antagonists for chemoprevention in patients with AR-positive and ER-negative DCIS could be considered.